Updated data on Litopterna from the Huayquerian Stage/Age (Late Miocene-Early Pliocene) of central-east Argentina - Schmidt, Gabriela Ines; Montalvo, Claudia I.; Cerdeño Serrano, Maria Esperanza; Sostillo, Renata; Tomassini, Rodrigo Leandro; Bonini, Ricardo Adolfo (Elsevier France-Editions Scientifiques Medicales Elsevier, 2022)
Hitherto, only the Proterotheriidae Ameghino, 1887 litopterns from the Cerro Azul Formation (Chasicoan-Huayquerian Stages/Ages; Late Miocene-Early Pliocene) in La Pampa Province had been studied, recognizing Proterotheriidae indet. at Cerro La Bota, Diplasiotherium pampa Soria, 2001 at several localities, Eoauchenia primitiva Ameghino, 1887 at El Guanaco, and cf. Brachytherium cuspidatum Ameghino, 1883 at Salinas Grandes de Hidalgo, which added to Epecuenia thoatherioides Cabrera, 1939 from Laguna Epecuén in Buenos Aires Province; this locality also yielded the Macraucheniidae Gervais, 1855 Huayqueriana cristata (Rovereto, 1914). Now, we enlarge the study to both litoptern families and to the outcrops of the Cerro Azul Formation in Buenos Aires Province. Concerning Macraucheniidae, we recognize: Scalabrinitherium bravardi Ameghino, 1883 at Salinas Grandes de Hidalgo, Telén, and Guatraché (La Pampa), and Laguna Epecuén (Buenos Aires); Paranauchenia denticulata Ameghino, 1891, Promacrauchenia sp., and Cullinia sp. at Salinas Grandes de Hidalgo and Laguna Chillhué (La Pampa); cf. Oxyodontherium zeballosi Ameghino, 1883b at Laguna del Monte (Buenos Aires); and Promacrauchenia sp. at Cantera Relleno Sanitario (Buenos Aires). Referring to Proterotheriidae, new results reveal the first record of Diplasiotherium pampa in Buenos Aires (Arroyo El Venado) and Neobrachytherium sp. at Laguna Epecuén and Laguna La Paraguaya (Buenos Aires). The litoptern diversity is close to that from the Lower Member of the Ituzaingó Formation, Late Miocene, Entre Ríos Province. The litoptern record does not provide confident data to support or reject the established relative biostratigraphic succession of localities of the Cerro Azul Formation, which is mainly based on some rodent lineages.